Gender Dysphoria in the Context of Compulsory Livelihood in Islam: Building Bridges Between Tradition and Social Change - Budiya, Bahroin; Smeer, Zeid Bin; Sumbulah, Umi (Dialogia, 2024)
This study aims to explain the experiences of people with gender dysphoria who seek to fulfill subsistence obligations in daily life, determine how religion handles them, and analyze the efforts of individuals and communities (in-laws and parents) in building bridges between tradition and social change. This research uses a case study method with a qualitative approach to understand the experience of individuals with gender dysphoria in fulfilling their income obligations in the Islamic context and in the perspective of parents or in-laws. The finding of this study is that gender identity is not something that is completely influenced by the social environment, but is also caused by certain biological factors. People with gender dysphoria face challenges in fulfilling subsistence obligations, these challenges are caused by their discomfort with traditional gender roles and the discrimination they experience, Islam argues that husbands remain responsible for the living. However, some people with gender dysphoria have support from their parents or in-laws.